THE ACTIVITY OF CIRCULATING PROTEASOMES IN TUMOR AND PRECANCEROUS DISEASES OF THE HEAD AND NECK ORGANS - E. A. Sidenko; D. E. Mikhalev; G. V. Kakurina; O. V. Cheremisina; O. D. Baidik; E. L. Choynzonov; I. V. Kondakova (Сибирский онкологический журнал)
Introduction. Identification of persons with a high oncological risk to squamous cell carcinoma of the head and neck region is an urgent problem for the early diagnosis of this disease. The activity of circulating proteasomes can be a criterion for predicting the risk of the larynx and oral cavity cancers in patients with precancerous diseases of the upper respiratory and gastrointestinal tracts. The aim of the study is to investigate the chymotrypsin-like and caspase-like activities of circulating serum proteasomes depending on the localization of precancerous and neoplastic diseases of the larynx and oral cavity. Material and Methods. The study population consisted of 35 patients with histologically verified HNSCC (T1–3N0–3M0), 15 patients with chronic hyperplastic laryngitis (CHL) and oral leukoplakia, and 10 healthy volunteers  who did not have chronic upper respiratory tract diseases in the acute stage. The median age of the patients was 53 ± 5.3 years. Results. An increase in the studied proteasome activities was found in the blood serum of patients with malignant tumors as compared with patients with chronic hyperplastic diseases associated with precancerous changes, as well as in the larynx and oral cavity cancers groups as compared with healthy donors. At the same time, depending on the localization of the pathological process, it was shown that only the chymotrypsin-like activity of the circulating pool of proteasomes significantly differs both in the groups of oral cancer leukoplakia, and in the groups of laryngeal cancer chronic hyperplastic laryngitis with dysplastic epithelial lesions. In addition, differences were found between chymotrypsin-like and caspase-like activities of circulating serum proteasomes in patients with chronic hyperplastic laryngitis with oral dysplasia and leukoplakia. Conclusion. The results obtained indicate that the determination of the CTp activity of the circulating pool of proteasomes can be used as a criterion for predicting the risk of the larynx and oral cavity cancers in patients with  precancerous diseases of the larynx and oral cavity.